Answers

2015-02-27T14:28:20+05:30
Since roots are equal, therefore Discriminant D=0 => (2+m)Square - 4( -mSquare - 4m - 4) = 0 => (m+2)Square + 4(mSquare + 4m + 4) =0 => (m+2)Square + [4(m+2)Square]=0 => (m+2)Square + [2(m+2)]Square=0 => (m+2)Square [1+2] =0 => 3(m+2)Square=0 => m+2=0 => m= -2 .
0
2015-02-27T17:35:59+05:30
Since roots are equal, therefore Discriminant D=0 => (2+m)Square - 4( -mSquare - 4m - 4) = 0 => (m+2)Square + 4(mSquare + 4m + 4) =0 => (m+2)Square + [4(m+2)Square]=0 => (m+2)Square + [2(m+2)]Square=0 => (m+2)Square [1+2] =0 => 3(m+2)Square=0 => m+2=0 => m= -2 
0